Synthesis of Fluorine Doped Zinc Oxide Particles by Hydrothermal Method - Kerli, S.; Alver, U.; Yaykasli, H.; Avar, B.; Tanriverdi, A.; Kursun, C. (Asian Journal of Chemistry, 2013)
Fluorine doped ZnO particles were prepared by a simple hydrothermal technique in an autoclave at 200 ºC for 4 h. Obtained particles were annealed at 600 ºC and their physical properties were investigated. X-Ray diffraction measurements reveal that ZnO:F particles contain a wurtzite and simonkolleite structure. Thermal gravimetric measurements show that thermal decomposition of simonkolleite occurs at above 600 ºC. SEM images of particles show that the morphologies change from a flower-like structure to a rose-like structure with increasing fluorine concentration. Optical measurements revealed that absorbance edge values of fluorine doped ZnO particles are blue shifted.